Maritime footprints: examining the maritime cultural landscape of Masirah Island, Oman, past and present - Blue, Lucy; Al-Jahwari, Nasser Said; Staples, Eric; Giorgio, Lorena; Croce, Paolo; Ghidoni, Alessandro; Al Busaidi, Ayyoub Nagmoush; Belfioretti, Luca (Proceedings of the Seminar for Arabian Studies, 2014)
This interdisciplinary paper explores the potential of the maritime cultural landscape approach to a recent preliminary study of the island of Masirah in south-eastern Oman. Masirah Island is known for its extended occupation and rich archaeological record and in particular for its intensive use of marine resources from the Neolithic period up to the modern day. The Maritime Footprints project sets out to explore this dynamic maritime cultural landscape through a variety of methodologies. It employs a range of terrestrial and maritime archaeological survey techniques and approaches, mapping selected sites, their geographical context, and associated coastal features; it undertakes maritime ethnographic inquiry, studying the traditional boats, their use and change over time; it records oral traditions and explores memory and practice relating to the sea and maritime activities. Three case studies are identified to explore the changing maritime cultural landscape of the island from prehistory to the modern day in order to reveal a more nuanced appreciation of maritime activity, seafaring, and changing use of the marine resource over time and between the island’s two geographically distinct coastlines. Essentially, this project aims to identify the maritime character of Masriah Island noting continuity and change over time and space.